Pengembangan Aplikasi Mobile Web Pengelolaan Gudang Kain (Studi Kasus: CV Sidodadi Textile) - Kevin Haidar; Agi Putra Kharisma; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Companies engaged in distribution utilize warehouses as temporary storage places for goods. The use of warehouses certainly has several procedures that must be applied so that goods are managed properly. In the practice of warehouse management, there are several processes that are carried out before the goods are distributed to customers. Based on interviews and observations that have been made, CV Sidodadi Textile experienced several main obstacles, including recording incoming and outgoing goods manually, causing difficulty in managing documents and archives of incoming and outgoing goods. From the problems that exist in the CV Sidodadi Textile, this research offers a solution by developing a mobile web-based fabric warehouse management application that is used for recording data such as incoming goods, outgoing goods, stock of goods, and the position of placing goods which was developed using the waterfall model. This study found 20 functional requirements, 2 non-functional requirements, and 5 actors. This application was developed using the laravel framework. The results of the tests that have been carried out on the mobile web application are validation testing getting the results of the predicate 100% passed, compatibility testing getting the results that the application can run on both iOS and Android mobile browsers, and usability testing getting results with excellent predicates on every aspect of the User Experience Questionnaire (UEQ).